Analysis of the Role of Cosmetic Dermatology in Improving the Quality of Life of Patients with Vitiligo: Observational Study at Busan Hospital, South Korea - Kim Soohyuk; Moon Kaeun (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Vitiligo is an autoimmune disease that causes skin depigmentation. This can have a significant impact on the patient's quality of life. Dermatological cosmetics can be used to cover depigmented areas and improve the patient's quality of life. Methods: This observational study was conducted on vitiligo patients treated at Busan Hospital, South Korea. Patients were given a questionnaire to assess their quality of life before and after using dermatology cosmetics. A total of 250 research subjects took part in this study. Data were analyzed using appropriate statistical tests. Results: The results showed that the use of dermatological cosmetics significantly improved the quality of life of vitiligo patients. Patients report improvements in self-satisfaction, self-image, and social interactions. Conclusion: Cosmetic dermatology is a safe and effective therapeutic option to improve the quality of life of vitiligo patients.